1998
DOI: 10.1042/bj3290539
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the ability of nucleophosmin/B23 to bind ATP

Abstract: By taking advantage of its ability to be retained by ATP-agarose, we have demonstrated that nucleophosmin/B23 is capable of binding ATP. The specificity of the binding was confirmed by the absence of significant binding to AMP-agarose and by its loss when nucleophosmin/B23 in nuclear extracts was preincubated with ATP. Preincubation of the nuclear extracts with other ribonucleotide triphosphates (GTP, CTP, UTP) did not compete for the binding of nucleophosmin/B23 to ATP-agarose. The purified recombinant nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Although protein B23 is capable of binding ATP (32), extensive studies in our laboratory have never detected any significant ATPase activity in the protein itself under any conditions. 2 Thus, it is unlikely that the affinity of B23 for a substrate is regulated by direct nucleoside triphosphate hydrolysis.…”
Section: Figmentioning
confidence: 84%
See 2 more Smart Citations
“…Although protein B23 is capable of binding ATP (32), extensive studies in our laboratory have never detected any significant ATPase activity in the protein itself under any conditions. 2 Thus, it is unlikely that the affinity of B23 for a substrate is regulated by direct nucleoside triphosphate hydrolysis.…”
Section: Figmentioning
confidence: 84%
“…Incorporation of 32 P from [␥-32 P]ATP into the complex catalyzed by CK2 was monitored in the linear phase of the reaction (Fig. 1A).…”
Section: Binding Of Denatured Substratementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro functional studies suggest that NPM displays chaperone-like behaviors on a wide variety of denatured substrates: (i) NPM inhibits temperaturedependent and independent protein aggregation, due to thermal denaturation, protecting enzymes from loss of activity; (ii) NPM promotes renaturation of chemically denatured proteins and it appears to preferentially bind denatured substrates through the exposure of hydrophobic regions in both NPM and substrates (Szebeni and Olson, 1999). Although NPM binds ATP, at least in vitro (Chang et al, 1998), its binding to substrates is governed by association-dissociation thermodynamics, and release of the substrate does not require ATP hydrolysis (Szebeni and Olson, 1999), as seen with other molecular chaperones including Hsp70 and chaperonins (Ruddon and Bedows, 1997). Interestingly, it has been shown that phosphorylation of NPM by casein kinase II induces the release of denaturated substrates (Szebeni et al, 2003).…”
Section: Nucleophosmin (Npm) Is a Multi-functional Cellular Chaperonementioning
confidence: 99%
“…Positively charged lysine residues in the C-terminus of B23 have been implicated in binding negatively charged ATP. 69 Mutation of lysine residues into asparagines disrupts B23 binding to ATP. Similarly, B23(K194N,K200N) and B23(K228N,K234N) mutants completely lost the binding activity to PIP3 compared to wild-type B23.…”
Section: Phosphatidylinositol Lipids Bind To B23mentioning
confidence: 99%